2021
DOI: 10.1186/s12889-021-10424-5
|View full text |Cite
|
Sign up to set email alerts
|

Birth cohort-specific trends of sun-related behaviors among individuals from an international consortium of melanoma-prone families

Abstract: Background Individuals from melanoma-prone families have similar or reduced sun-protective behaviors compared to the general population. Studies on trends in sun-related behaviors have been temporally and geographically limited. Methods Individuals from an international consortium of melanoma-prone families (GenoMEL) were retrospectively asked about sunscreen use, sun exposure (time spent outside), sunburns, and sunbed use at several timepoints ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In contrast to sunburn prevalence rates in the US, a study also found that the frequency of sunburns in birth cohorts relative to 1910-1919 only increased with each subsequent birth cohort until 1950-1959, which may indicate that either secular trends in sunburn prevalence do not reflect cohort trends or that international trends do not reflect trends specific to the US [34]. The study did find increased tanning bed use with each subsequent birth cohort [34], which could reflect tanning attitudes. Starting in the 1920s, tanned skin began to become desirable and led to the use of artificial UVR (tanning beds) in the late 1970s [11].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In contrast to sunburn prevalence rates in the US, a study also found that the frequency of sunburns in birth cohorts relative to 1910-1919 only increased with each subsequent birth cohort until 1950-1959, which may indicate that either secular trends in sunburn prevalence do not reflect cohort trends or that international trends do not reflect trends specific to the US [34]. The study did find increased tanning bed use with each subsequent birth cohort [34], which could reflect tanning attitudes. Starting in the 1920s, tanned skin began to become desirable and led to the use of artificial UVR (tanning beds) in the late 1970s [11].…”
Section: Discussionmentioning
confidence: 56%
“…Another study reported that the prevalence of sunburns did not decrease among adolescents and their parents between 1998 and 2004, even though sunscreen use increased [12,33]. In contrast to sunburn prevalence rates in the US, a study also found that the frequency of sunburns in birth cohorts relative to 1910-1919 only increased with each subsequent birth cohort until 1950-1959, which may indicate that either secular trends in sunburn prevalence do not reflect cohort trends or that international trends do not reflect trends specific to the US [34]. The study did find increased tanning bed use with each subsequent birth cohort [34], which could reflect tanning attitudes.…”
Section: Discussionmentioning
confidence: 84%
“…This alarming trend is further amplified by the elevated intensity of sunbed use and its prevalence among young adults and women, suggesting the need for targeted interventions for these high-risk groups. Although stricter regulations are leading to a global decline in sunbed use, individuals with a family history of melanoma demonstrate worryingly increased sunbed use and no decrease in overall sun exposure [ 44 ]. This highlights the need for more effective strategies beyond broad sun-safety campaigns to address this specific risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…However, encouraging trends are emerging in sun protection behaviors, with increased sunscreen use and reduced sunburns among younger generations. While these positive developments are crucial, continued efforts are required to address the heightened risks associated with family history [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A birth cohort analysis of melanoma-prone families demonstrates changes in sun protection behaviour and sunburns over time. People from 17 centres in Europe, North and South America, Australia and the Middle East ( n = 2407) were questioned about sun exposure and sunburns at various anchor points across their lives [ 153 ]. These behaviours were analysed according to birth cohort (in decades from those born in the 1910s and 1920s through to those born in the 1980s).…”
Section: Harms Of Exposure To Uv Radiationmentioning
confidence: 99%